When
,
![10^(2\cdot1 - 1) + 1 = 10^1 + 1 = 11](https://img.qammunity.org/2023/formulas/mathematics/college/thhonuspwwc5417oibi25pr9t271igycz6.png)
which is of course divisible by 11.
Assume this holds for
, that
![11 \mid 10^(2k - 1) + 1](https://img.qammunity.org/2023/formulas/mathematics/college/xhcqln4oseol3sgucy71jh01t0l90scx44.png)
In other words,
![10^(2k - 1) + 1 = 11\ell](https://img.qammunity.org/2023/formulas/mathematics/college/8ko8t697hnx0sp3x7surk0o9csq3gb5vlp.png)
for some integer
.
Use this to show the claim is true for
.
![10^(2(k+1) - 1) + 1 = 10^(2k + 1) + 1 \\\\ ~~~~~~~~~~~~~~~~~~~~ = 10^(2k+1) + \left(10^(2k-1) + 10^(2k-1)\right) + 1 \\\\ ~~~~~~~~~~~~~~~~~~~~ = \left(10^(2k+1) - 10^(2k-1)\right) + \left(10^(2k-1) + 1\right) \\\\ ~~~~~~~~~~~~~~~~~~~~ = 10^(2k-1) \left(10^2 - 1\right) + 11\ell \\\\ ~~~~~~~~~~~~~~~~~~~~ = 99*10^(2k-1) + 11\ell \\\\ ~~~~~~~~~~~~~~~~~~~~ = 11\left(9*10^(2k-1) + \ell\right)](https://img.qammunity.org/2023/formulas/mathematics/college/z4wnfzw3zul0rzsa91fxrxui2h9r2nakvz.png)
which is indeed divisible by 11. QED
On the off-chance you meant
, notice that
is odd for any integer
. Similarly
is odd for all
, so the above proof actually proves this automatically.